Implikasi Pengelolaan Kelas Bilingual Terhadap Peningkatan Mutu Siswa Sekolah Menengah Pertama MTs. Hidayatul Muttallimin Sidoarjo - M. Athoiful Fanan; M.Ripin Ikhwandi; Halimatul Munawaroh (ICO EDUSHA, 2022)
This study was conducted to examine the implications of bilingual classroommanagement on improving the quality of students in MTs Hidayatul MuttalliminSidoarjo with the aim to find out how the management of bilingual classes in MTsHidayatul Muttallimin Sidoarjo, how to improve the quality of students in MTsHidayatul Muttallimin Sidoarjo, and how the implications of bilingual classmanagement on improving the quality of students at MTs Hidayatul MuttalliminSidoarjo. This type of research uses quantitative research. And data collection is doneby questionnaire, observation, interview and documentation. Then the data is analyzedusing a statistical formula, namely: the formula of the formula and the formula ofproduct moment and coupled with the regression formula. The results of this study,show that the management of the bilingual class MTs Hidayatul Muttallimin Sidoarjo inthe implementation process can run effectively and efficiently or is classified as good,because the percentage calculation results show between 56% -100%. And improvingthe quality of students in MTs Hidayatul Muttallimin Sidoarjo after entering thebilingual class has increased in the achievement of sufficient performance results, thisis based on the calculation of the percentage of questions peritem the value obtained isbetween 56% -75% with criteria classified as sufficient.While in its implications the management of bilingual classes in MTs HidayatulMuttallimin Sidoarjo has positive implications (impacts / effects) on improving thequality of students in high or strong categories. This, based on the product momentcalculation results, the results obtained are 0.71 and the barada interpretation table atthe value of r = 0.70 - 0.90 indicates that between variables X and Y there are strong orhigh implications. Likewise with the results of the calculation of the regression formulashows that the management of bilingual classes has a positive relationship withimproving the quality of students with a value of 0.711.